Comparison of Dobutamine and Treadmill Exercise Echocardiography in Detecting and Predicting the Extent of Coronary Artery Disease - Islam, Lohani Md Tajul; Sultana, Sarjana; Awal, Towhidur Rahman; Islam, Nayla; Islam, Md Ridwanul; Jobayer, Mohammad (University Heart Journal, 2025)
Background: Coronary artery disease (CAD) continues to be a major cause of morbidity and mortality worldwide. Timely and precise detection is essential for appropriate intervention and management. Two commonly used non-invasive diagnostic techniques for detecting coronary artery disease are dobutamine stress echocardiography and treadmill exercise echocardiography. This study aimed to compare the effectiveness of dobutamine and treadmill exercise echocardiography for detecting coronary artery disease. Methods: This prospective observational study was conducted at the Department of Cardiology, Bangabandhu Sheikh Mujib Medical University, Dhaka, Bangladesh from January 2000 to December 2021. As study subjects, a total of 77 suspected patients of coronary artery disease were enrolled by using a purposive sampling technique. For data analysis MS Office tools and SPSS Version 23.0 were used. Results: In comparing the peak hemodynamic data during dobutamine echocardiography and treadmill exercise electrocardiography, we found statistically significant differences (p<0.05). Additionally, significant differences were observed between the procedures in HR (beats/min), SBP (mm Hg), DBP (mm Hg), mean BP (mm Hg), % max HR, and PRR (mmHg) × HR/100. Significant differences were also found in both maximal and submaximal stress assessments (p<0.001). . Conclusion: Echocardiography performed immediately after treadmill exercise induces a greater ischemic burden than dobutamine-atropine infusion. Therefore, in clinical settings where it is feasible, exercise echocardiography should be preferred over dobutamine echocardiography for diagnosing ischemia. University Heart Journal 2024; 20(2): 56-60